Macrophages-Related Genes Biomarkers in the Deterioration of Atherosclerosis - Zheng, Yue; Qi, Bingcai; Gao, Wenqing; Qi, Zhenchang; Liu, Yanwu; Wang, Yuchao; Feng, Jianyu; Cheng, Xian; Luo, Zhiqiang; Li, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background: Macrophages are involved in all stages of cardiovascular diseases, demonstrating the correlation between inflammation, atherosclerosis and myocardial infarction (MI). Here our aim is to investigate macrophages-related genes in the deterioration of atherosclerosis. Methods: GSE41571 was downloaded and the abundance of immune cells were estimated utilizing the xCell. Utilizing the limma test and correlation analysis, differentially expressed macrophages-related genes (DEMRGs) were documented. Functional pathways and the protein-protein interaction network were analyzed and the hub DEMRGs were obtained. The hub DEMRGs and their interactions were analyzed using NetworkAnalyst 3.0 and for validation, the hub DEMRGs expressions were analyzed using the GSE135055 and GSE116250 datasets as well as atherosclerosis and MI mice model. Results: 509 differentially expressed genes were correlated with the abundance of macrophages and were identified as DEMRGs (PCC > 0.6), which were mainly enriched in extracellular structure organization, lysosomal membrane, MHC protein complex binding and so on. After screening out, 28 hub DEMRGs were obtained with degrees ≥20, including GNAI1 (degree = 113), MRPS2 (degree = 56), HCK (degree = 45), SOCS3 (degree = 40), NET1 (degree = 28) and so on. After validation using GEO datasets and the atherosclerosis and MI mice model, the 8 proteins were validated using ApoE-/- and C57 mice. The expression levels of proteins, including SYNJ2, NET1, FZD7, LCP2, HCK, GNB2 and PPP4C were positively correlated to LVEF, while that of EIF4EBP1 was negatively correlated to LVEF. Conclusion: The screened hub DEMRGs, SYNJ2, NET1, FZD7, LCP2, HCK, GNB2, EIF4EBP1 and PPP4C, may be therapeutic targets for treatment and prediction to the patients with plaque progression and MI recurrent events. The kit of the 8 hub DEMRGs may test plaque progression and MI recurrent events and help diagnose and treat MI-induced HF, thus decreasing mortality and morbidity.